Solve the following radical equation: √(x-3) + 5 = x

Reset Selection

Thank you for the opportunity to help you with your question!

ANSWER IS

D. {7}

√(x-3) + 5 = x

√(x-3) = x-5

squaring both sides

x-3 = (x-5)^2

x-3 = x^2 - 10x+25

x^2 - 10x+25-x+3 = 0

x^2 -11x +28 = 0

x^2 - 4x-7x+28 = 0

x(x-4) - 7 ( x -4) =0

x- 7 = 0

x=7

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up